Childhood Neglect rather than Abuse Is More Strongly Associated with Anhedonia across Major Depression and Obsessive-Compulsive Disorder Patients and University Students - Fan, Jie; Han, Yan; Xia, Jie; Wang, Xiang; Liu, Qian; Liu, Yao; Lu, Jingjie; Yu, Quanhao; Yang, Yanjie; Zhu, Xiongzhao (Depression and Anxiety, 2023)
Background. According to the dimensional model of adversity, the deprivation and threat dimensions of CT influence distinct neural circuits and have different developmental outcomes. The present study compared neglect and abuse subtypes which are representative of deprivation and threat dimensions of CT prediction of anhedonia in MDD and OCD patients and university students. Methods. A total of 305 patients with MDD, 152 patients with OCD, and 2110 university students fulfilled the Childhood Trauma Questionnaire to identify neglect and abuse subtypes of CT. Different aspects of anhedonia were measured. Hierarchical linear regression analysis was conducted to identify subtypes of trauma as predictors of different aspects of anhedonia in MDD and OCD patients and university students, respectively. Results. Childhood neglect, not abuse, showed association with anticipatory and state anhedonia in OCD patients and anticipatory, consummatory, physical, and state anhedonia in MDD patients and university students. Both childhood neglect and abuse were associated with social anhedonia in university students, but the neglect type showed greater magnitude. In terms of more specific categories, emotional neglect was the type of CT demonstrating strongest magnitude of association with most of the anhedonia aspects. Conclusions. Findings revealed that deprivation, rather than threat, was the more influential adversity dimension for the individuals’ anhedonia presentations.